EKSPLORASI JENIS-JENIS LEBAH MADU TAK BERSENGAT DI KEPULAUAN ARU - Kwalepa, Santy; Tan, Lieke; Lamerkabel, Jacobus (MARSEGU : Jurnal Sains dan Teknologi, 2024)
Exelation aims to find what types of stingless honey bees are there in the Aru Islands. The research was carried out on the Aru Islands, Wamar Island (Wangel and Durdiela Village), Kobror Island (Warbola and Benana Village), and Koba Island (Mutrai and Koba Village) from March to July 2022. The method used in preciation in Vata is a descriptive method, namely identifying stingless honey bees through observation, morphological characteristics and measurements, morphometrics and describing the location of the eccomium. Research shows that stingless honey bee stings were found. In Kalman Aru there were 36 active colonies at a height of 1-241 cm, with nesting sites found namely cave cavities, stone cavities and Ulouran rates. The average morphometric character of Tetragonula capens worker stratum bees found was long. body 374-4 25mm, head width 177-1 81mm. head space 1 47-1 55mm, wing length 3.81-4-35mm, antenna length 170-173mm, while Tetragonula cobalteata which was found, body length 278-324mm, head width 1 18-132 mm, head length 109-123 mm wing length and tegula 316-3.22 mm, and antenna length 2 18-2.22 mm.